Uncommon Neurosyphilis: Subacute Meningomyelitis with Distinctive “Candle Guttering Appearance” - Liwen Wang; Jing Fang; Juan Wang (Indian Journal of Radiology and Imaging)
In this article, we presented an exceedingly rare clinical case of neurosyphilis, radiological revealed a distinctive “candle guttering appearance.” Posttreatment for syphilis, both clinical symptoms and radiological markers showed complete resolution.